2013
DOI: 10.1016/j.gaceta.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de contactos según círculos concéntricos en un caso de tuberculosis laríngea

Abstract: Laryngeal tuberculosis involved high transmission to coworkers and frequenters of the town bar. In-depth studies through concentric circles and good communication with exposed individuals should be carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Through interviews with the bars’ owners, 58 habitual customers were located and their possible exposure evaluated. The global prevalence of LTBI observed in customers of the three bars (51·7%) was high and similar to that observed in other investigations [13, 14, 24, 25]. Bars are very popular establishments in Spain and should be evaluated and, if possible, studied in contact investigations by applying a social network approach where necessary.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Through interviews with the bars’ owners, 58 habitual customers were located and their possible exposure evaluated. The global prevalence of LTBI observed in customers of the three bars (51·7%) was high and similar to that observed in other investigations [13, 14, 24, 25]. Bars are very popular establishments in Spain and should be evaluated and, if possible, studied in contact investigations by applying a social network approach where necessary.…”
Section: Discussionsupporting
confidence: 84%
“…There is considerable evidence about the presence of customers affected by TB in bars [13, 14, 24–27]. The investigation confirmed that the index patient had spent an average of 6 h a week in three bars in his neighbourhood.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations